Image, ethics and children. An analysis of NGOs' Facebook posts dedicated to children - Collado Alonso, Rocío (2024)
The protection of children is a priority obligation in our societies. This study focuses on the delicate field of photographic representation of minors to analyze how their images achieve connections with the people who follow the publications of these organizations. The research aims to question and analyze the secondary victimization of vulnerable minors and the relationship of this treatment with public engagement. A descriptive analysis methodology is applied to the photographs published in the posts of the official Facebook pages of four NGOs dedicated to children. The research finds that boys and girls usually appear as protagonists of the information, but occupying almost 20 percent of the cases the role of victims. The image of girls is used more than boys, and their representation as victims and sufferers is the one that provokes the most engagement. However, the study shows that what generates the most engagement with audiences is merely illustrative and non-dramatic photography of minors, one that avoids symbolic revictimization and allows visual cultures of peace in which children can inhabit positively.